qanda-logo
search-icon
root-icon-orangeSímbolos
Problema
solution-image
Resuelve los ejercicios, guíate por los primeros tres ejemplos. $1.$ $mn\right)\left(mn\right)=-\left(-mn\right)\left(mn\right)=\left(m+n\right)\left(m+n\right)=\left(+m\right)\left(nm\right)=m^{2}$ $2$ $25c^{2}-36d^{2}$ $36d^{2}$ $=\left(5c+6d\right)\left(5c-6d\right)$ $3$ $\left(3x+4y\right)\left(3x-4y\right)=9x^{2}$ $-16y^{2}$ $4$ $\left(x+4\right)\left(x-4\right)=$ $5$ $\left(-12m-3n\right)\left(12m-3n\right)=$ $6$ $x^{2}$ $225y^{2}$
Secundaria
Otra
Búsquedas: 107
Solución
answer-user-profile-image
Profesor de Qanda - Brincel
answer-reply-image